HUMAN CIRCULATORY SYSTEM MODEL MEDIA AND INTERACTIVE VIDEOS TO OVERCOME LEARNING DIFFICULTIES IN HUMAN CIRCULATORY SYSTEM MATERIAL FOR GRADE V STUDENTS OF SRENGAT 01 ELEMENTARY SCHOOL - Syifaa Ulinnuha Santosa; Anas Thohir; Fadella Winanda Putri Sari; Satria Wahyu As'ari (Jurnal Pembelajaran Sains, 2022)
The Human Circulation System is problematic because it explains how work requires innovation so students can receive it well. Lack of media causes students’ difficulties in learning. The purpose of this study was to identify learning difficulties in the Human Circulatory System material and determine the effectiveness of the Human Circulatory System media model and interactive videos in overcoming student learning difficulties in this material in fifth-grade students at SD Negeri Srengat 01. The data collection method used in This research is a test with ten indicator questions. This study's data analysis method is descriptive statistics to analyze students' learning difficulties. The results of the pre-test analysis showed that students had learning difficulties. However, after being given treatment and analyzing the results of the post-test, it was found that the Human Circulatory System media and interactive videos greatly influenced student learning outcomes. It was proven from 10 question indicators, 8 of which experienced an increase. In addition, from the pre-test average of 41.17 it increased to 57.92 on the post-test average. This shows that the media model of the human circulatory system and interactive videos effectively overcome student learning difficulties, judging from the results of the post-test, which are better than before. This research has implications for the use of authentic media and digital media.